A novel p.Val244Leu mutation in MFN2 leads to Charcot-Marie-Tooth disease type 2. Issue 1 (December 2016) - Yang, Yuan; Li, Ling
Abstract Background Charcot-Marie-Tooth (CMT) disease is one of the most common hereditary peripheral neuropathy. The major clinical features of CMT are progressive muscle weakness of distal extremities and sensory loss.MFN2 encodes a GTPase dynamin-like protein mitofusin 2 and plays an essential role in mitochondrial functions. In previous studies, MFN2 mutations have been linked to neurological disorders including CMT type 2 (CMT2). Here, we report a novel mutation inMFN2 which leads to CMT 2. Case presentation We report a 4-year-old Chinese boy with CMT symptoms including foot-drop gait, running difficulties, frequent falls, slowly progressive atrophy of lower legs with a mildly foot deformity. Nerve conduction velocity study (NCVS) found that no compound motor action potential (CMAP) was elicited in the nervi suralis and tibial nerve. Moreover, the sensory nerve action potential (SNAP) of the nervi suralis was not elicited, which means the peripheral nerves of his lower limbs were damaged. Targeted next-generation sequencing identified a novel heterozygous mutation c.730G > C (p.Val244Leu) inMFN2 in the patient but not in his parents, suggesting that this mutation likely occurredde novo . c.730G > C (p.Val244Leu) inMFN2 is a likely pathogenic mutation for CMT2. Conclusion The c.730G > C (p.Val244Leu) mutation inMFN2 is a likely pathogenic mutation for CMT2.